The evaluation of different embryo markers and their subsequent effect on embryo development, implantation and pregnancy outcome in an in-vitro fertilization program - Kotze, Dirk Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.